Comparison of student learning outcomes using artificial intelligence and physics textbooks on harmonic vibration material - Tri Upi Hajarwati Juldial; Yuvita Oktarisa; Tresna Galih Sukma Suryana (HAFECS PRESS, 2025)
Technological advances in the digital era have brought significant changes in the world of education, including in physics learning methods. This study aims to analyze the learning outcomes of students who use Artificial Intelligence (AI) and physics textbooks on harmonic vibration material. The study used a quantitative method with a quasi-experimental design of the control group pretest-posttest type. The study population was all students of class XI FA in one of the high schools in Serang Regency. The sample consisted of two classes selected purposively, namely XI FA 1 as the experimental class and XI FA 2 as the control class, each with 34 students. The instrument was in the form of 15 multiple-choice questions based on Bloom's Taxonomy (C1–C4) which had been tested for validity, reliability, difficulty level, and distinguishing power. The experimental class received AI-based learning, while the control class used a physics textbook. The results of statistical tests using SPSS 30.0 showed significant differences between the two classes with a significance value of 0.038 <0.05. The average posttest score of the experimental class was 82.72 (very high category), while the control class was 76.64 (high category). This shows that AI-based learning is more effective in helping to understand physics concepts, especially complex concepts such as harmonic vibrations. However, textbooks still have an important role in building conceptual understanding. Therefore, AI should be used as a complement, not a substitute for textbooks, to optimize student learning outcomes in physics learning. Abstrak. Kemajuan teknologi di era digital telah membawa perubahan signifikan dalam dunia pendidikan, termasuk dalam metode pembelajaran fisika. Penelitian ini bertujuan menganalisis perbandingan hasil belajar siswa yang menggunakan Artificial Intelligence (AI) dan buku teks fisika pada materi getaran harmonik. Penelitian menggunakan metode kuantitatif dengan desain quasi-eksperimental tipe control group pretest-posttest. Populasi penelitian adalah seluruh siswa kelas XI FA di salah satu SMA di Kabupaten Serang. Sampel terdiri dari dua kelas yang dipilih secara purposive, yaitu XI FA 1 sebagai kelas eksperimen dan XI FA 2 sebagai kelas kontrol, masing-masing 34 siswa. Instrumen berupa 15 soal pilihan ganda berdasarkan Taksonomi Bloom (C1–C4) yang telah diuji validitas, reliabilitas, tingkat kesukaran, dan daya pembeda. Kelas eksperimen mendapatkan pembelajaran berbasis AI, sedangkan kelas kontrol menggunakan buku teks fisika. Hasil uji statistik menggunakan SPSS 30.0 menunjukkan perbedaan signifikan antara kedua kelas dengan nilai signifikansi 0,038 < 0,05. Rata-rata nilai posttest kelas eksperimen adalah 82,72 (kategori sangat tinggi), sedangkan kelas kontrol 76,64 (kategori tinggi). Hal ini menunjukkan bahwa pembelajaran berbasis AI lebih efektif dalam membantu pemahaman konsep fisika, terutama konsep kompleks seperti getaran harmonik. Meskipun demikian, buku teks tetap memiliki peran penting dalam membangun pemahaman konseptual. Oleh karena itu, AI sebaiknya digunakan sebagai pelengkap, bukan pengganti buku teks, untuk mengoptimalkan hasil belajar siswa dalam pembelajaran fisika.